Structure of the CaMKIIδ/Calmodulin Complex Reveals the Molecular Mechanism of CaMKII Kinase Activation - Rellos, Peter (Public Library of Science, 2010)
Long-term potentiation (LTP), a long-lasting enhancement in communication between neurons, is considered to be the major cellular mechanism underlying learning and memory. LTP triggers high-frequency calcium pulses that result in the activation of Calcium/Calmodulin (CaM)-dependent kinase II (CaMKII). CaMKII acts as a molecular switch because it remains active for a long time after the return to basal calcium levels, which is a unique property required for CaMKII function. Here we describe the crystal structure of the human CaMKIIδ/Ca(2+)/CaM complex, structures of all four human CaMKII catalytic domains in their autoinhibited states, as well as structures of human CaMKII oligomerization domains in their tetradecameric and physiological dodecameric states. All four autoinhibited human CaMKIIs were monomeric in the determined crystal structures but associated weakly in solution. In the CaMKIIδ/Ca(2+)/CaM complex, the inhibitory region adopted an extended conformation and interacted with an adjacent catalytic domain positioning T287 into the active site of the interacting protomer. Comparisons with autoinhibited CaMKII structures showed that binding of calmodulin leads to the rearrangement of residues in the active site to a conformation suitable for ATP binding and to the closure of the binding groove for the autoinhibitory helix by helix αD. The structural data, together with biophysical interaction studies, reveals the mechanism of CaMKII activation by calmodulin and explains many of the unique regulatory properties of these two essential signaling molecules. ENHANCED VERSION: This article can also be viewed as an enhanced version in which the text of the article is integrated with interactive 3-D representations and animated transitions. Please note that a web plugin is required to access this enhanced functionality. Instructions for the installation and use of the Web plugin are available in Text S1.